Draft Genome Sequence of Aliivibrio fischeri Strain 5LC, a Bacterium Retrieved from Gilthead Sea Bream (Sparus aurata) Larvae Reared in Aquaculture - Califano, Gianmaria (Genome Announc, 2015)
To shed light on the putative host-mediated lifestyle of the quintessential marine symbiont Aliivibrio fischeri, and on the symbiosis versus potentially pathogenic features of bacteria associated with farmed fish, we report the draft genome sequence of A. fischeri strain 5LC, a bacterium retrieved from gilthead sea bream (Sparus aurata) larvae.